2020
DOI: 10.1002/jbio.201960140
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is improved in high‐fat fed mice by photobiomodulation therapy at 630 nm

Abstract: Photobiomodulation therapy (PBMT) in the infrared spectrum exerts positive effects on glucose metabolism, but the use of PBMT at the red spectrum has not been assessed. Male Swiss albino mice were divided into low‐fat control and high‐fat diet (HFD) for 12 weeks and were treated with red (630 nm) PBMT or no treatment (Sham) during weeks 9 to 12. PBMT was delivered at 31.19 J/cm2, 60 J total dose per day for 20 days. In HFD‐fed mice, PBMT improved glucose tolerance, insulin resistance and fasting hyperinsulinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 103 publications
1
17
0
Order By: Relevance
“…The light power was measured with a calibrated detector (Newport 918D-ST-SL wand detector from 400 to 1100 nm; Newport Corp., Irvine, CA, USA) and power meter (Newport 1936-R; Newport Corp., CA, USA). Based on previous reports of PBM regarding improved glucose intolerance [ 7 , 8 , 9 , 10 ] and the availability of LED chips for application to a catheter in our laboratory, we used an LED with wavelengths of 630 nm and 850 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The light power was measured with a calibrated detector (Newport 918D-ST-SL wand detector from 400 to 1100 nm; Newport Corp., Irvine, CA, USA) and power meter (Newport 1936-R; Newport Corp., CA, USA). Based on previous reports of PBM regarding improved glucose intolerance [ 7 , 8 , 9 , 10 ] and the availability of LED chips for application to a catheter in our laboratory, we used an LED with wavelengths of 630 nm and 850 nm.…”
Section: Methodsmentioning
confidence: 99%
“…External photobiomodulation (PBM) with light-emitting diode (LED) in rat or mouse models may result in improved glucose tolerance, insulin resistance and fasting hyperinsulinemia, and regeneration of the pancreas and liver in previous animal models [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. External PBM also reduced adiposity and inflammatory infiltrate in adipose tissue [ 7 , 13 , 14 ]. This effect may be associated with increased adenosine triphosphate in mitochondria and biological response in cells by PBM [ 15 ]; however, it is not clearly proven [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental animal research (Table 3) supports the beneficial effects of PBM applied before and after exercise in physical activity, through improved performance in endurance training [78,79], decreased level of proinflammatory cytokines [80][81][82][83][84], positive effects on aerobic metabolism [85,86], oxidative stress [86][87][88] and increased ATP [89,90]. Histopathological examination performed after PBM showed that it can protect myonecrosis, reduce pro-inflammatory cell infiltration, muscle destruction, inflammation and can help accelerate tissue repair [91][92][93].…”
Section: Discussionmentioning
confidence: 84%
“…In another report, Silva et al, 21 do show that insulin resistance is improved in high-fat fed mice who undergo photobiomodulation therapy at 630 nm. They concluded this after studying male Swiss albino mice divided into low-fat control and high-fat diet for 12 weeks and who were treated with red (630 nm) PBMT or no treatment (Sham) during weeks 9 to 12.…”
Section: Resultsmentioning
confidence: 92%